A Process of Ethical Subjectivation in Forming Subjectivities in Teenage Mothers - Prakongpan, Peeradet; Sankatiprapa, Kittikorn; Tharawan, Kanokwan (Journal of Community Development Research (Humanities and Social Sciences); Vol 13 No 3 (2020): July - September 2020, 2020)
These preliminary results of narrative inquiry are based on the data collected as part of a doctoral dissertation, which concentrated on how some young mothers are able to form new subjectivities and resist dominant discourses on teenage mothers in Thailand. To understand this process, Michel Foucault’s concept of the ethical self is employed along with an examination of the discourses of teenage mothers in Thailand. Ethical subjectivation is a process in which individuals decide to reconstruct their identity reflecting on a perceived moral dilemma. In the case of teenage mothers, this ethical concept usually involves aspects of the ideal mother and a discourse on motherhood in Thai society. Six teenage mothers who appeared to possess an ethical self were selected for this qualitative study. Each mother was invited to share her life story using an in-depth interview. The stories were analyzed through an analysis of narratives and applied a thematic analysis to find common themes among the participants. These results indicated three types of ethical mothers: “Buddy mom”, “Two-in-one parent” and “Traditionally-oriented mother”. However, these types of subjectivity can change over time depending on the individual and, at times, may appear simultaneously. Keywords: Ethical Subjectivation, Teenage Mother Discourses, Analysis of Narratives